2023
DOI: 10.1002/14651858.cd013588.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for patent ductus arteriosus (PDA) in preterm infants: an overview of Cochrane Systematic Reviews

Abstract: Background Patent ductus arteriosus (PDA) is associated with significant morbidity and mortality in preterm infants. Several non‐pharmacological, pharmacological, and surgical approaches have been explored to prevent or treat a PDA. Objectives To summarise Cochrane Neonatal evidence on interventions (pharmacological or surgical) for the prevention of PDA and related complications, and interventions for the management of asymptomatic and symptomatic PDA in preterm infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 177 publications
0
16
0
Order By: Relevance
“…Moreover, previous evidence has shown that medical treatment is more effective in closing a PDA than no treatment. 35 Fourth, since there is no guideline for PDA management in China, there may be significant variability in clinical practices, which may bias the results. Finally, despite the fact that we made a rigorous adjustment for confounding factors, unmeasured confounders may still affect our results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous evidence has shown that medical treatment is more effective in closing a PDA than no treatment. 35 Fourth, since there is no guideline for PDA management in China, there may be significant variability in clinical practices, which may bias the results. Finally, despite the fact that we made a rigorous adjustment for confounding factors, unmeasured confounders may still affect our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found cerebral ultrasound Doppler useful in the evaluation of PDA in prematures [ 17 , 18 ]. PDA in premature infants is associated with morbidity and mortality but the prevention and treatment of the open duct is still a controversial and challenging topic [ 19 ]. The hemodynamic understanding of the transitional period of premature infants needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Sung et al showed that delayed ligation (after more than 2 weeks after birth) decreased the risk for mortality or morbidities in extremely preterm infants born at 23-25 weeks of gestation [37]. Therefore, as a method that can be performed immediately after the birth of preterm infants and is minimally invasive, the transcatheter closure of PDA for preterm infants weighing less than 2 kg has been reportedly successful in a small number of institutions [38][39][40]. Considering the optimization of outcomes for long-term neurodevelopment, we hope that new, feasible, and effective treatments for this PDA will become widespread in the future.…”
Section: Discussionmentioning
confidence: 99%